Effect of different water stress days during reproduction phase on the yield of beans - Magalhães, Arnóbio Anselmo de; Millar, Agustín A. (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted to study the drought tolerance of beans (Phaseolus vulgaris L.) cultivar IPA-74-19) when submitted to different water strees days during the reproduction phase. At the Bebedouro Experimental Station, EMBRAPA, Petrolina-PE, Brazil, an experiment was set up using randomized complete block with 9 treatments and 3 replicates. Thetreatments consisted of different water stress days startling at the beginning of flowering. In all the treatments, the irrigation was maintained at optimum level before and after the water stress period. At harvest, grain yield, number of pods per plant, and number of grains per pod were obtained. For grain yield, significative difference was found between treatments at 0.01 level. For pods per plant, and grain per pods data, significative differences were found between treatments at 0.05 and 0.01 levels, respectively. Yield reduction of 20%was observed when the crop was kept 14 days without irrigation. After 17 and 20 days without irrigation yield reductions of 38 and 52 %, respectively, were observed. After 20 days yield reduction remained constant until 29 days of water stress. Using the period of greatest response to water stress, it is possible to obtain the relationship between relative yield and soil matric potential, which is important to define the operational level for irrigation management.